Analisis Penerimaan Sistem E-Personal Di Bbvet Maros Dengan Menggunakan Techology Acceptance Model (TAM) - SUPARYATI SUPARYATI (Sekolah Tinggi Teknik - PLN, 2019)
This study analyzes the acceptance of the E-Personal System at the Maros Center for Veterinary Medicine using the Technology Acceptance Model (TAM) method. In TAM, it is mentioned that two beliefs, namely perceptions of usability (POU) and perceptions of ease of use (PEU) determine interest in behavior to use the Information System. Beliefs about the use of systems that will improve performance are called perceptions of usability (POU), while beliefs about system ease in their use are called perceptions of ease of use (PEU). Analysis of E-Personal acceptance in this study is the context of acceptance by the user. What the user in this study meant was an employee at the Maros Veterinary Center who had the obligation to run E-Personal. The analysis is focused on the user's perception of the E-Personal that they must run. The perceptions of the users analyzed were user perceptions about the ease of use of E-Personal and the user's perception of the benefits of E-Personal. The study was conducted at the E-Personal of the Maros Veterinary Center. The respondents of this study were 48 respondents from various levels of rank and class. The results showed that Perceived Usefulness affected the use of E-Personal, while the Perceived Ease of Use did not affect.